2007
DOI: 10.1371/journal.pone.0000623
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Activation of Complement and Coagulation by MBL-Associated Serine Protease 2

Abstract: The complement system is an important immune mechanism mediating both recognition and elimination of foreign bodies. The lectin pathway is one pathway of three by which the complement system is activated. The characteristic protease of this pathway is Mannan-binding lectin (MBL)-associated serine protease 2 (MASP2), which cleaves complement proteins C2 and C4. We present a novel and alternative role of MASP2 in the innate immune system. We have shown that MASP2 is capable of promoting fibrinogen turnover by cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
212
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 239 publications
(232 citation statements)
references
References 35 publications
(40 reference statements)
6
212
0
3
Order By: Relevance
“…It has been shown that MASP-1 is the main activator of MASP-2 Heja et al, 2012; Megyeri et al, 2013) and that MASP-2 is able to cleave prothrombin (Krarup et al, 2007). Therefore, we wanted to test whether the effects of MASP-1 on clotting observed in WB and PPP could be due to MASP-1-mediated activation of MASP-2 and not due to direct action of MASP-1 itself.…”
Section: Effects Of Masp-1 Are Prothrombin-dependentmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been shown that MASP-1 is the main activator of MASP-2 Heja et al, 2012; Megyeri et al, 2013) and that MASP-2 is able to cleave prothrombin (Krarup et al, 2007). Therefore, we wanted to test whether the effects of MASP-1 on clotting observed in WB and PPP could be due to MASP-1-mediated activation of MASP-2 and not due to direct action of MASP-1 itself.…”
Section: Effects Of Masp-1 Are Prothrombin-dependentmentioning
confidence: 98%
“…In the lectin pathway, mannose binding lectin (MBL) and ficolins recognize target molecules on foreign and/or altered surfaces and thereby induce activation of the MBL-associated serine proteases (MASPs) MASP-1, MASP-2, and MASP-3 (Krarup et al, 2007). MASPs 1-3 and the enzymatically inactive MBL-associated proteins MAp19 and MAp44 are alternative splicing products from two genes: MASP-1/MASP-3/Map44 and MASP2/MAp19 (Stover et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the functions of the other MASPs are poorly understood, MASP-1 appears to play a role as an amplifier of complement activation (6, 7). Additionally, MASP-1 is able to cleave fibrinogen to fibrin, whereas MASP-2 is able to generate active thrombin by cleavage of prothrombin (8,9). No conclusive biological function has yet been attributed to MASP-3 and sMAP.…”
mentioning
confidence: 99%
“…Similarly, MASP-1 can also activate TAFI (Hess et al, 2012b) which inhibits fibrin-dependent fibrinolysis by tissue plasminogen activator (t-PA). It was reported earlier that MASP-2 is able to activate prothrombin (Krarup et al, 2007).…”
Section: Masp-1 Interacts With Coagulation Factors and Affects Clot Fmentioning
confidence: 85%